Um método baseado em cruzamentos por zero para localização de faltas de alta impedância em redes aéreas de distribuição - HUAQUISACA PAYE, Juan Carlos (Universidade Federal do Pará, 2024)
The location of High-Impedance Faults (HIFs) is an increasingly relevant reliability issue in the electric power distribution industry. The development of practical and accurate single-terminal fault locating methods is vital for reducing the time and cost of restoring long-duration interruptions. However, the need to estimate both the parameters of the fault model and the fault current signal can compromise the accuracy and practicality of existing HIF location methods. This is due to the larger number of parameters that need to be estimated when a HIF model is included in the formulation, as well as the assumption that load currents at the network bars are constant during a pre- and post-HIF interval. In other words, the use of the fault model and waveform implies that the location method depends on the random characteristics and magnitudes of the fault current, which are determined by environmental, technical conditions, and the type of surface where the HIF occurs, including even the way the contact between the surface and the conductor occurs. This thesis proposes a fault-model-free iterative method based on zero-crossings of signals to locate HIFs in overhead distribution networks. Two insights on voltage signal relationships are provided to eliminate the need to estimate fault model parameters and the fault current signal in the HIF location process. The first insight is based on zero-crossings of the calculated voltage drop per unit length signal to estimate two parameters of the voltage signal at the fault point. The other insight is based on the zero-crossing of the voltage signal at the fault point, where the two parameters were previously estimated, to calculate the fault distance from the k-th node. Simulation results on a modified IEEE 34-node test feeder validate the high accuracy and robustness of the proposed method, considering the effect of various factors on the estimation of the HIF distance. Additionally, the convergence performance of the proposed method is evaluated